Determination of spare part consumption based on wear of friction surfaces in agricultural machinery - Irgashev Amirkul; Irgashev Bekhzod; Barakayev Fazliddin (E3S Web of Conferences)
This study presents a methodology for determining the consumption of spare parts (specifically gear wheels, ball bearings, roller bearings, and spline joints) used in cotton tractors operating under high-dust environmental conditions. The methodology is based on the limit wear of friction surfaces in these components. The paper examines the causes of roughness, friction, wear, and failure of spare part surfaces due to atmospheric influences such as dust, humidity, load, stress, and wear products. Additionally, the study explores the ability of these spare parts to function effectively in an oily environment. By analyzing wear resistance and calculating permissible wear thresholds, the research provides insights into optimizing spare part consumption to maintain tractor performance and reliability.